GEOMAGNETIC EFFECTS ON TIME-INTEGRATED COSMOGENIC NUCLIDE PRODUCTION WITH EMPHASIS ON IN SITU 14C AND 10BE - Pigati J.S.; Lifton N.A. (My University, 2004)
Production of cosmogenic nuclides (CNs) in geologic material is a function of the cosmic-ray flux at the Earth's surface, which in turn is a function of the intensity and orientation of the Earth's geomagnetic field. Temporal variations in the intensity of the geomagnetic field and the position of the geomagnetic dipole axis (i.e., polar wander) must be considered when calculating production rates that are integrated through time. We have developed a model, based in part on protocols set forth by Desilets and Zreda [Earth Planet. Sci. Lett. 206 (2003) 21-42], that accounts for these variations in an effort to systematically determine their impact on time-integrated production of short-lived (in situ 14C; t1/2=5.73 ka) and long-lived (in situ 10Be; t1/2=1.5 Ma) CNs. Our modeling results show that for samples exposed for the last 3 ka, integrated in situ 14C and 10Be production rates that account for temporal variations in the intensity of the Earth's geomagnetic field are up to ∼13% lower than modern rates at the same location [modern rates are referenced to the 1945.0 Definitive Geomagnetic Reference Field (DGRF)]. In contrast, intensity-corrected 10Be rates are up to ∼30% higher than modern for samples exposed for >25-30 ka. Intensity variations have little effect (<5%) on integrated CN production for samples exposed for the last 15-20 ka, regardless of site location or nuclide used.